Síntese hidrotermal de sodalita básica a partir de um rejeito de caulim termicamente ativado - Paz,Simone Patrícia Aranha da (2010)
Basic sodalite was successfully synthesized by hydrothermal method using kaolin waste as source of Aluminum and Silicon. This waste is mainly composed by kaolinite and is produced in large amount by kaolin processing industries for paper coating from the Amazon region. Initially, the waste has been calcined at 700 ºC for 2 h and then reacted with the following solutions: Na2CO3 and mixture of Na2CO3 + NaOH to 150 ºC with autogenous pressure for 24 h. The raw materials and transformed materials were characterized by XRD, FTIR and SEM. In both studied media, well-crystallized, basic sodalite was the only phase synthesized, while in the literature usually a mixture of zeolites is obtained.